Integration in times of economic decline. Migrant inclusion in Southern European societies: trends and theoretical implications. Issue 14 (26th October 2018) - Finotelli, Claudia; Ponzo, Irene
ABSTRACT: Despite the large amount of literature on migrants' integration, little is known about integration in times of economic decline. The aim of this Special Issue is to contribute to filling this research gap by exploring the nexus between the Great Recession that began in 2008 and integration processes. To this end, we regard Southern European countries as an observatory of crucial relevance because of their harsh experience of the crisis and common social and policy patterns that make their comparative analysis empirically sound and theoretically significant. In order to offer some general views on this Issue's contributions and to highlight some of the explanatory potential of this collective work, we frame the collected articles by referring to different dimensions of integration: (i) residence status and political rights; (ii) socio-economic conditions; and (iii) perceptions of migrants and the receiving society. Contributions show that in Southern Europe the legal-political and cultural dimensions of integration, i.e. legal status and perceptions towards migrants, have apparently been more resilient to the crisis than the economic dimension, such as the socio-economic conditions of migrants.